'Being Able to Breathe Again': The Effects of Cash Transfer Programmes on Psychosocial Wellbeing. Issue 8 (2nd August 2016) - Samuels, Fiona; Stavropoulou, Maria
Abstract: The multidimensional nature of poverty and vulnerability and the role of psychosocial dimensions in achieving wellbeing are increasingly being recognised, yet development programme assessments still tend to focus on material outcomes. We situate this article within a wellbeing framework and after reviewing evidence on the psychosocial effects of cash transfer programmes, we explore findings from a qualitative and participatory study on beneficiary experiences of unconditional cash transfers in the Middle East and Sub-Saharan Africa. Narratives reveal how cash transfers can improve psychosocial wellbeing at individual level and in relation to others suggesting that psychosocial dimensions need to be considered when planning, implementing and evaluating cash transfer programmes.